The Worlding of Arabic Literature Language, Affect, and the Ethics of Translatability. - Stanton, Anna Ziajka (Fordham University Press, 2023)
This book examines the translation of Arabic literature into English, in conversation with contemporary literary scholarship and classical Arabic aesthetic and linguistic paradigms. Case studies reveal practices of translating that activate embodied forms of language and affective modes of reception to position Arabic literature ethically in the world literary system.